Ẓafār, capital of Ḥimyar sixth preliminary report, February - March 2006 - Franke, Kristina A.; Rösch, Manfred 1952-; Ruppert-Asaad, Cornelia I. E.; Yule, Paul 1947- (2008)
Die Grabungen konzentrierten sich am südwestlichen Hangfuß des Ḥuṣn Raydān, wo die Erhaltungsbedingungen günstig zu sein schienen. Das Stone building wurde vielleicht erst um die Zeitenwende errichtet und existierte über 400 Jahre. Höhepunkte bilden die Entdeckung lebensgroßer Plastiken. Fossile sabäo-ḥimyarische Ortsnamen wurden kartiert. Die Charakterisierung ḥimyarischer bildenden Künste als dekadent ist eine grobe Vereinfachung.
Excavations took place at the south-western foot of the Ḥuṣn Raydān, where preservation seemed favourable. The Stone building may have been built around the time of Christ und was in use over 400 years. Highlights include the discovery of life-size human depictions. Fossil Sabaeo-Ḥimyarite place-names were mapped. The general characterisation that the Ḥimyarite period visual arts as decadent is a vast oversimplification.
ركزت التنقيبات على أسفل المنحدر الجنوبي الغربي لحصن ريدان، حيث بدا أن حالة حفظ البقايا هناك مواتية. ولربما كان ‹البناء الحجري› قد شُيّد حوالي بداية التقويم الميلادي وكان قائما لأكثر من أربعمائة سنة. ويشكل العثور على تماثيل بالحجم الطبيعي ذروة المكتشفات. وقد كان من الممكن تحديد أسماء قديمة لأماكن سبئية-حميرية على الخارطة. ويمكن اعتبار وصف الفنون التشكيلية الحميرية بأنها متدهورة تبسيطا فظّا
Keywords: Ḥimyar